Kinerja Balai Pelestarian Cagar Budaya (BPCB) Provinsi Jambi Dalam Upaya Peningkatan Pelestarian Benda Cagar Budaya Berbasis Kearifan Lokal di Muaro Jambi - Hapsa; Firmansyah Putra (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
This article describes the performance of the government, especially the Jambi provincial government in preserving cultural heritage objects. Jambi Province is one of the provinces that has a wealth of historical heritage, especially those scattered in Muaro Jambi Regency. Cultural heritage objects (BCB) are regional local assets which, if managed optimally, can brand the area with positive values and serve as educational tours that have an impact on regional income. So it is important to know the extent of the efforts made by the local government in maintaining and maximizing the preservation of cultural heritage objects. The method used is qualitative, to describe the findings in the field. The local government seeks to maximize performance both in terms of quantity, quality, and effectiveness in preserving BCB based on local wisdom by collecting data and conservation, archaeological exhibitions, ancient FGDs, ancient vlog competitions, technical guidance, and restoration. Not only concerned with economic interests alone (regional income) but more than that, namely maintaining historical heritage that can be passed on to the next generation, as evidence of civilization in the footsteps of Jambi Province.